Polyostotic Fibrous Dysplasia Mimicking Metastatic Disease Radiographically: A Case Report and Literature Review - Gay, MD, David; Philip, MD, Joey; Ahmed, MD, Shahida; Choe, MD, Jin; Cai, MD, PhD, Donghong (North American Journal of Medicine and Science, 2017)
Fibrous dysplasia is a benign intramedullary lesion characterized by an excessive proliferation of cellular fibrous tissue intermixed with irregular trabeculae. It involves any of the bones presenting as monostotic, polyostotic, or panostotic lesion. It is caused by mutation in the GNAS1 gene (20q13.2, encoding a G-protein) resulting in inhibition of intrinsic GTPase activity of Gs alpha protein. The timing of mutation in the developmental course determines the extent of the disease, in which an earlier mutational event leads to a wider distribution of mutant cells, and consequently a more severe course of the disease. We report a case of polyostotic fibrous dysplasia in a 58-year-old male with CT scan revealing multiple lucent and sclerotic areas in bilateral ribs and iliac bones. A metastatic process was suspected by radiologists. However, a bone marrow biopsy from left posterior iliac crest demonstrated a bland fibroblastic proliferation admixed with irregular metaplastic bone in a collagenized stroma. By pyrosequencing of alpha subunit of G-protein, a mutation in Arg201(p. R201H; c.602G>A) was detected. All the findings supported a diagnosis of polyostotic fibrous dysplasia. The present case highlights a rare clinical incidental disease with radiographic mimic of metastatic process. [N A J Med Sci. 2017;10(1):21-24. DOI: 10.7156/najms.2017.1001021]